Ethnobotanical survey of medicinal plants used by Malayali tribes in Jawadhu hills of Eastern Ghats, Tamilnadu, India - Magendiran, M.; Vijayakumar, K. K. (Journal of Medicinal Herbs and Ethnomedicine, 2022)
An ethnobotanical survey was carried out to collect information from the Malayali tribes of Jawadhu hills, Thiruvannamalai district, Tamilnadu, India from August 2016 to July 2017. A total of 63 plant species belonging to 32 families were distributed into 55 genera, which were commonly used by the local Malayali tribes for the treatment of various diseases such as headaches, fevers, asthma, coughs, colds, wounds, snake bites, piles, stomach disorders, skin diseases, gastric ulcers, kidney stones, urinary infection, diabetes, jaundice, inflammation etc. In the present study, Acanthaceae, Euphorbiaceae, Amaranthaceae, and Asclepiadaceae are the most dominant families used in the treatment of various ailments. Generally, leaves are used to prepare herbal medicine. The ethnomedicinal plants used by the Malayali tribes were arranged alphabetically followed by botanical name, family, local name, medicinal uses and mode of administration.